Fine mapping and candidate gene analysis of the floury endosperm gene, FLO(a), in rice - Qiao, Yongli; Lee, Song-I; Piao, Rihua; Jiang, Wenzhu; Ham, Tae-Ho; Chin, Joong Hyoun; Piao, Zhongze; Han, Longzhi; Kang, Si-Yong; Koh, Hee-Jong (Elsevier, 2010)
In addition to its role as an energy source for plants, animals and humans, starch is also an environmentally friendly alternative to fossil fuels. In rice, the eating and cooking quality of the grain is determined by its starch properties. The floury endosperm of rice has been explored as an agronomical trait in breeding and genetics studies. In the present study, we characterized a floury endosperm mutant, flo(a), derived from treatment of Oryza sativa ssp. japonica cultivar Hwacheong with MNU. The innermost endosperm of the flo(a) mutant exhibited floury characteristics while the outer layer of the endosperm appeared normal. Starch granules in the flo(a) mutant formed a loosely-packed crystalline structure and X-ray diffraction revealed that the overall crystallinity of the starch was decreased compared to wild-type. The FLO(a) gene was isolated via a map-based cloning approach and predicted to encode the tetratricopeptide repeat domaincontaining protein, OsTPR. Three mutant alleles contain a nucleotide substitution that generated one stop codon or one splice site, respectively, which presumably disrupts the interaction of the functionally conserved TPR motifs. Taken together, our map-based cloning approach pinpointed an OsTPR as a strong candidate of FLO(a), and the proteins that contain TPR motifs might play a significant role in rice starch biosynthetic pathways.